Cultura turística y desarrollo sostenible en la comunidad de Manacamiri, 2023 - Pinto Manzanares, Goretty Milagros (2024)
The main purpose of this research was to determine the relationship between tourist culture and sustainable development in the community of Manacamiri, 2023. To do this, an applied correlational methodology and non-experimental design was used. The sample was made up of 152 families from said community, and a questionnaire was applied as a measurement instrument. Through this means, the following results were obtained: The tourist culture is regular (32%), due to the environmental problems generated by tourist activity and the lack of interest and predisposition to solve them and propose organizational ideas. For its part, the level of sustainable development is regular (30%), since sometimes there are many families dedicated to tourism and this benefits other economic activities. However, there are never plans or programs to preserve protected areas. Finally, a fairly strong positive correlation of 0.858 was determined between tourism culture and sustainable development and a significance of 0.000.